Losses and use efficiencies along the phosphorus cycle. Part 1: Dilemmata and losses in the mines and other nodes of the supply chain - Scholz, Roland W.; Wellmer, Friedrich-Wilhelm (Resources, conservation and recycling, 2015)
•Losses and efficiency management are key means for phosphorus/resources management.•Efficiency is a means, efficacy the primary goal and effectiveness the overall utility.•Residues from mining and beneficiation are large and may ask for special attention.•We need strategies for increasing net use efficiency and total resource use efficiency.•Defining cut-off grades asks for special attention from a sustainability perspective. This contribution provides a set of definitions and relates the concepts of losses, efficiencies, efficacy, and effectiveness (which is conceived as a kind of overall utility) in general and for the case of phosphorus. We show how the material—technical and economic value-related definitions are linked and can be utilized for sustainable phosphorus and resource management. Part 1 provides an overview of global anthropogenic and natural phosphorus flows and identifies major losses from the current phosphorus supply–demand chain. We discuss in what way the concepts of efficacy, efficiency, and effectiveness are related and how they may be used for assessing aspects of sustainable management. We discuss losses in mining and consider how management of the mining rate, cut-off grade, and stripping ratio might affect losses today and in the future. Although we identify critical losses of the supply–demand chain, the back sections of the paper focuses on losses in mining and beneficiation. When introducing different types of losses, we illuminate whether the residues in mining should be perceived as losses and whether mining companies can increase the total resource efficiency by decreasing the cut-off grade (i.e., by decreasing the concentration of phosphate ore that becomes subject to mining and beneficiation). This is discussed from an intergenerational justice and external costs perspective of losses. We introduce a classification system for (i) highly probable or definite absolute losses, (ii) losses from the supply–demand chain that become deferred losses, and (iii) uncertain losses that may become subject to sustainable resource management. This classification may be applied to all nodes of the supply–demand chain. We elaborate on how these types of losses can become subject to sustainable resource management. Part 2 of the paper discusses various operationalizations, fallacies, and challenges related to applying different efficiency terms.